Utilisasi Penumpukan Peti di Depo Peti Kemas - Asep Ali Thabah; Rahmanda Iman Putra (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2014)
Based on the analysis of Queing Theory, the utilisation of the first location A.04.1 shows that the crate box 2.21/day (λ1), the crate box 0.2217/day (m1), 4.75 % (r1) and the crate box of the second location A.04.2 is 5.93/day (λ2), 0,3788 the crate box/day (m2), and 7,45% (r2). These results show that the utilisation of the two locations are below of what is expected. In this case, the research has provided the solutions which are to increase the traffic or volume of the crate and increase the marketing of the location utilisations using 4P’s (Product, Price, Promotion, Place).